Enhancing Employee Performance in The Hospitality Industry: The Role of Information Technology, Soft Skills, and Integrated Management Information Systems - Ni Putu Rita Suliastari; Pande Ketut Ribek; Putu Agus Eka Rismawan (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
This study aims to analyze the influence of Information Technology, Soft Skills, and Integrated Management Information Systems on Employee Performance at Quest Hotel San Denpasar. The phenomenon underlying this study is a decline in employee performance due to the suboptimal implementation of the Integrated Management Information System (IMIS), a less-than-intuitive system interface, and weak employee communication skills in serving guests. This study employs a quantitative approach using a survey method. The study population consists of all 43 employees at Quest Hotel San Denpasar, with a saturated sampling technique ensuring the entire population serves as the sample. Data were collected via a questionnaire that had been tested for validity and reliability. Data analysis utilized multiple linear regression. The results of the study indicate that: Information technology has a positive and significant effect on employee performance. Soft skills and the integrated management information system have a positive and significant effect on employee performance. Simultaneously, all three variables have a significant effect on employee performance. This study recommends that the company enhance employee soft skills development and optimize the implementation of the integrated management information system to improve employee performance.